MBRS-39. TWIST1 PLAYS A REGULATORY ROLE IN MEDULLOBLASTOMA METASTASIS. Issue 2 (22nd June 2018) - Cardall, Alice; Nasir, Aishah; Linke, Franziska; Grabowska, Anna M; Kerr, Ian D; Coyle, Beth
Abstract: Paediatric medulloblastoma (MB) are frequently metastatic, resulting in a poor prognosis for the patient. Little is known about the underlying mechanisms; therefore, our ability to develop novel therapeutic approaches is limited. We hypothesise that, despite medulloblastomas being neuro ectodermal in origin, they metastasise via an epithelial-mesenchymal transition (EMT) -like pathway, mediated by the EMT transcription factor TWIST1. TWIST1 protein and gene expression were analysed in patient tissue microarrays by immunohistochemistry and in MB cell lines by qRT-PCR respectively. Bioinformatic analyses using Genomatix and R2: Genomics Analysis and Visualization Platform were used to further investigate the role of TWIST1 and predict candidate target genes. The functional and physical interactions between TWIST1 and the multidrug transporter ABCB1 were investigated using 3D migration and invasion models of metastatic D283MED (TWIST1 positive) and TWIST1-transfected MED6 cells and by chromatin immunoprecipitation (ChIP). High TWIST1 expression was associated with metastatic MB patients (p≤0.05) and group 3 metastatic cell lines. Genomatix analysis predicted a TWIST1 binding site was present in the ABCB1 promoter. This was confirmed by ChIP analysis of D283MED cells (p≤0.05). Overexpression of TWIST1, in TWIST1-transfected MED6 cells, resulted in the formation of large cell aggregates (a metastatic phenotype), which could be inhibited by vardenafil (ABCB1 inhibitor; p≤0.05). Vardenafil was also able to attenuate aggregation of D283MED cells (p≤0.05). Other potential TWIST1-target genes are also currently under investigation. Our data reveals a key regulatory role for TWIST1 during MB metastasis. TWIST1 target genes, including ABCB1, offer potential novel therapeutic targets for metastatic MB.